Arsenic and antimony co-contamination influences on soil microbial community composition and functions: Relevance to arsenic resistance and carbon, nitrogen, and sulfur cycling. (August 2021) - Li, Yongbin; Zhang, Miaomiao; Xu, Rui; Lin, Hanzhi; Sun, Xiaoxu; Xu, Fuqing; Gao, Pin; Kong, Tianle; Xiao, Enzong; Yang, Nie; Sun, Weimin
Graphical abstract: Highlights: Mining activity of realgar ore resulted in co-contamination of As and Sb. Mining activity also influenced microbial structure and metabolic potentials. As and Sb co-contamination enriched some As- and Sb-resistant bacteria. The contamination affected As-related genes, and others about C, N, and S cycling. Abstract: Microorganisms can mediate arsenic (As) and antimony (Sb) transformation and thus change the As and Sb toxicity and mobility. The influence of As and Sb on the innate microbiome has been extensively characterized. However, how microbial metabolic potentials are influenced by the As and Sb co-contamination is still ambiguous. In this study, we selected two contrasting sites located in the Shimen realgar mine, the largest realgar mine in Asia, to explore the adaptability and response of the soil microbiome to As and Sb co-contamination and the impact of co-contamination on microbial metabolic potentials. It is observed that the geochemical parameters, including the As and Sb fractions, were the driving forces that reshaped the community composition and metabolic potentials. Bacteria associated with Bradyrhizobium, Nocardioides, Sphingomonas, Burkholderia, and Streptomyces were predicted to be tolerant to high concentrations of As and Sb. Co-occurrence network analysis revealed that the genes related to C fixation, nitrate/nitrite reduction, N fixation, and sulfate reduction were positively correlated with the As and Sb fractions, suggesting that As and Sb biogeochemical cycling may interact with and benefit from C, N, and S cycling. The results suggest that As and Sb co-contamination not only influences As-related genes, but also influences other genes correlated with microbial C, N, and S cycling.